The effect of planned presence of the family at the time of weaning on the length of weaning from mechanical ventilation in patients with brain injury admitted to intensive care units - Fatemeh Salmani; Maryam Moghimian; Mina Jouzi (BMC Nursing, 2022)
Abstract Background Weaning the patient from mechanical ventilation (MV) is one of the common treatments in intensive care units (ICU). Among the factors that can complicate the weaning process are psychological problems caused by a lack of family visits. Objective This study aimed to evaluate the effect of scheduled visiting on weaning from mechanical ventilation in patients with brain injury admitted to ICUs. Methods This quasi-experimental study was performed on 60 patients with brain injury referred to one of the hospitals in Central Province, Iran in 2020. The selection of samples based on inclusion criteria and random allocation to the two groups of intervention and control by permuted block randomization was done. The first-degree relatives of the patients at the time of weaning in the intervention group were present at the patient’s bedside twice a day at 10:00 AM and 3:00 PM for 30–45 min and performed what they had been trained to do. Participants in the control group visited patients from the area outside the patient room. Length of weaning, length of mechanical ventilation, and length of stay in the ICU were recorded and measured using a researcher-conducted checklist. The results were analyzed using descriptive and inferential statistics and chi-square and independent t-tests in SPSS16. Results The study results showed that the number of patients weaned from mechanical ventilation in the intervention group was significantly higher than that of the control group (P ≤ 0.05). The mean length of weaning in the intervention and control groups was not statistically significant, but it was clinically significant in the intervention group (P > 0.05). In addition, the length of mechanical ventilation and the length of stay of the intervention group in the ICU were significantly shorter than that of the control group (P ≤ 0.05). Conclusion According to the study results, scheduled visiting resulted in faster weaning from mechanical ventilation. As a result, nurse managers are suggested to make arrangements for family members to be present at the patient’s bedside in order for patients to be weaned off the mechanical ventilator more easily.